LINGUISTIC MARKERS OF VIEWPOINT IN PRESS DISCOURSE - Трофимчук, Анастасія (Current Issues of Foreign Philology, 2021)
The article is an attempt to identify the linguistic markers of viewpoint in English-language press. The first section deals with the notion of viewpoint, the way it is defined and divided into categories, plus with its possible linguistic manifestations within each category. Attention is focused on the classification proposed by Paul Simpson (1993), who differentiates four main categories of viewpoint: spatial, temporal, psychological, and ideological. The linguistic indicators of viewpoint in language are analyzed on the basis of the works by Simpson (1993) and Short (1996). The subsequent analysis is based on press discourse, namely a selection of excerpts from British and the American newspapers (The New York Times, The Washington Post, The Observer, The Independent). In the analysis, numerous indicators of viewpoint are identified and explained with respect to their type and significance. The results of the research allow one to conclude that press discourse, although apparently objective and factual, is heavily perspectivised through viewpoint indicators.